Scott at the opera: interpreting Das Opfer (1937) - Elizabeth Leane; Carolyn Philpott; Hanne Nielsen (2014)
In November 1937, an unusual work premiered at the Hamburg State Opera. Entitled Das Opfer (“The Sacrifice”), the one-act opera tells the story of Robert F. Scott’s last expedition, focusing on the famous final moments of Lawrence Oates. While the action features only four main characters, a large chorus – dressed for much of the time in penguin costumes – comments on events. The opera was an adaptation of an award-winning and controversial play by the eccentric expressionist poet Reinhard Goering. The libretto was written by Goering, who committed suicide not long after its completion – about a year before the first performance. The score was by composer Winfried Zillig – a student of Arnold Schoenberg and promoter of his radical modernist 12-tone technique. Subsequent descriptions of Das Opfer and its reception have been remarkably varied. Some commentators assert the play was quickly banned by the National Socialists due to its pro-British content and “degenerate” 12-tone score. Others argue that this version of events was invented post-war in order to distance Zillig from the Nazi regime, which actually embraced his work, including Das Opfer. Given that Das Opfer was probably the first professional musical response to Scott’s last expedition, and certainly the first operatic performance of the story, it is surprising that no in-depth contextual account of the work is available. The aim of our research is to provide an analysis of this opera – historical, textual and musical – that is both relevant to an Antarctic studies readership and accessible to English-speaking readers. In doing so, we suggest tentative answers to some questions raised by this intriguing musical work: How was Scott’s expedition, which has so often been tied to ideas of Britishness, adapted for German audiences? And what significance did the opera’s Antarctic setting hold in this context?